11.0k views
0 votes
If P(x)= x3 –x2+1, Then P(0)+P(1) =

User Gandarez
by
5.3k points

2 Answers

5 votes
The answer to this question is 2
User Mohammed Safeer
by
5.8k points
5 votes

Answer:


p(0) + p(1) = 2

Explanation:

=>
p(x) = x^3-x^2+1

Putting x = 0 in p(x)

=>
p(0) = (0)^3-(0)^2+1

=>
p(0) = 0-0+1

=>
p(0) = 1

Putting x = 1 in p(x)

=>
p(1) = (1)^3-(1)^2+1

=>
p(1) = 1-1+1

=>
p(1) = 1

So,

=>
p(0)+p(1) = 1+ 1

=>
p(0) + p(1) = 2

User John Tan
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.